UJI VARIABEL FEKUNDITAS, VARIABEL TKG DAN IKG DALAM SKALA RASIO KELAMIN PADA IKAN NOMEI (HARPODON NEHEREUS) - Muhammad Firdaus; Gazali Salim; Ermawaty Maradhy; Ira Maya Abdiani (Jurnal Harpodon Borneo, 2013)
Fish of nomei (Harpadon nehereus) which one of characteristic of Tarakan City because this fish is only found in the waters Juata of Tarakan City. Fish of Nomei has become one of the favorite food for the predators albino dolphin. In the event of the harvest is much, so in the waters around Tarakan City will be filled with a bunch of types of dolphins. This study aims to determine fecundity (number of eggs) in a spawning of fish nomei (Harpadon nehereus) in Tarakan, to determine the level of maturity of the gonads of fish nomei (Harpadon nehereus) in scale of the sex ratio, and to termine the gonads maturity index of fish nomei (Harpadon nehereus) in scale of the sex ratio. Number of samples were observed 479 males and 241 females fish of Nomei (Harpadon nehereus) taken 4 times in two months at 4 stations. Results of this study show from March-May 2013 fish of nomei male and female are still in the early reproductive period, estimated male and female fish nomei no one has done spawning ( TKG V ). Fecundity values seen in gonad maturity level four (TKG IV) in the range of the number of eggs get SD = 8171 + 4279 eggs (average of 8,167 eggs of fish nomei). In the gonads Maturity Index (IKG) fish species nomei male greatest gonad maturity index four (IKG IV), gonad maturity index of the smallest in the gonad maturity index (IKG I). Meanwhile, the gonads Maturity Index Index (IKG) Fish nomei greatest females in the fourth gonad maturity index (IKG IV), gonad maturity index of the smallest in the gonad maturity index ( IKG II). Keywords : IKG , TKG , fecundity , fish of nomei , Harpadon nehereus